1997
DOI: 10.1046/j.1471-4159.1997.68010370.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐Derived Neurotrophic Factor Increases the Stimulation‐Evoked Release of Glutamate and the Levels of Exocytosis‐Associated Proteins in Cultured Cortical Neurons from Embryonic Rats

Abstract: Differentiation and survival of neurons induced by neurotrophins have been widely investigated, but little has been reported about the long-term effect of brainderived neurotrophic factor (BDNF) on synaptic transmission. Among many steps of neurotransmission, one important step is regulated release of transmitters. Therefore, the release of glutamate and GABA from cortical neurons cultured for several days with or without BDNF was measured by an HPLC-fluorescence method. Although BDNF had little effect on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
63
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(76 citation statements)
references
References 28 publications
(25 reference statements)
12
63
0
Order By: Relevance
“…BDNF and NT 3 treatment in E16 dissociated and P7 slice hippocampal cultures results in an increase in the number of synaptic vesicles docked at active zones (Collin et al, 2001;Tyler and Pozzo-Miller, 2001). Consistent with these observations, several groups report that BDNF treatment of hippocampal and cortical neuronal cultures increase synaptobrevin expression (Takei et al, 1997;Tartaglia et al, 2001;Yamada et al, 2002). In accordance with the effects of exogenous neurotrophins, mice that are deficient in either BDNF or TrkB exhibit marked reductions in the total number of docked vesicles at hippocampal synapses and a redistribution of docked vesicles to areas far from the active zone in the cerebellar synapses (Martinez et al, 1998;Pozzo-Miller et al, 1999;.…”
Section: Neurotrophins As Synaptic Modulators: Presynaptic Terminal Fsupporting
confidence: 54%
“…BDNF and NT 3 treatment in E16 dissociated and P7 slice hippocampal cultures results in an increase in the number of synaptic vesicles docked at active zones (Collin et al, 2001;Tyler and Pozzo-Miller, 2001). Consistent with these observations, several groups report that BDNF treatment of hippocampal and cortical neuronal cultures increase synaptobrevin expression (Takei et al, 1997;Tartaglia et al, 2001;Yamada et al, 2002). In accordance with the effects of exogenous neurotrophins, mice that are deficient in either BDNF or TrkB exhibit marked reductions in the total number of docked vesicles at hippocampal synapses and a redistribution of docked vesicles to areas far from the active zone in the cerebellar synapses (Martinez et al, 1998;Pozzo-Miller et al, 1999;.…”
Section: Neurotrophins As Synaptic Modulators: Presynaptic Terminal Fsupporting
confidence: 54%
“…Thus, the 3-4-month estrogen deprivation in our VEH-treated mice may have diminished the response of BDNF to environmental stimuli. Interestingly, BDNF has previously been shown to promote presynaptic vesicle docking and increase the amount of synaptophysin per neuron (Lu and Chow, 1999;Pozzo-Miller et al, 1999a;Takei et al, 1997). Therefore, it is surprising that our enrichmentinduced increases in synaptophysin did not positively correlate with changes in BDNF levels.…”
Section: Effects Of Enrichment Alonementioning
confidence: 64%
“…For example, BDNF promotes phenotypic maturation of neocortical GABAergic neurons (Ip et al, 1993;Nawa et al, 1993;Croll et al, 1994;Marty et al, 1996;Reibel et al, 2000;Nagano et al, 2003). Exogenous and endogenous BDNF acts on developing GABAergic neurons to enhance the expression of glutamic acid decarboxylase (GAD), presynaptic proteins, and AMPA-type glutamate receptors as well as morphological differentiation (Mizuno et al, 1994;Jones et al, 1994;Takei et al, 1997;Narisawa-Saito et al, 1999a;Rutherford et al, 1998;Bolton et al, 2000). Gene manipulation studies have confirmed the facilitatory effects of BDNF on the neocortical GABAergic inhibition as well (Jones et al, 1994;Huang et al, 1999;Gorski et al, 2003).…”
Section: Introductionmentioning
confidence: 99%